Pawai Obor Dalam Memperingati Hari Isra Mi’raj Diiringi Tambua Masyarakat Nagari Pilubang - Ena Noveria; Fathan Nur Rasyadan; Kenny Aditiya; Fauzan Febrian; Febrian Wizar Pratama; Ezru Arya Aflah; Adrian Digo Pratama (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
The torch parade is a religious tradition that continues to be preserved by the community as a form of commemorating religious events and strengthening social cohesion. This activity aims to enhance reigious values, reinforce social solidarity, and preserve local culture within the community. The parade is held at night after religious activities at the mosque and involves participants from various age groups, ranging from children to adults. The implementation method consists of several stages, including planning, preparation, execution, and closing, using a participatory approach. KKN students actively collaborate with the community in every stage, from coordination and torch-making using simple materials such as bamboo and coconut fiber to the execution of the parade. Data collection techniques include observation, interviews, and documentation, while data analysis is conducted descriptively. The results indicate that the torch parade was carried out smoothly, orderly, and safely according to the planned arrangements. The event was also enlivened by traditional tambua tasa music, which enhanced participants’ enthusiasm and attracted community attention. In addition to its religious function, the torch parade symbolizes the light of faith and reflects values of togetherness, mutual cooperation, and social solidarity. This activity provides benefits in religious, social, and cultural aspects. Future efforts should focus on improving planning, ensuring safety, and encouraging youth participation to sustain and develop this tradition in the future.